KARAKTERISTIK IBU RUMAH TANGGA DENGAN HIV AIDS DI RUMAH SAKIT UMUM - Tri Hastuti; Djaswadi Dasuki; Dhesi Ari Astuti (Universitas Aisyiyah Yogyakarta, 2017)
Abstract: The new paradigm of UNAIDS Global goal is Zero AIDS - related death, this can be achieved if patients come to HIV care and get ARV therapy as soon as possible. The purpose of this study is to know the characteristics of housewives with HIV AIDS. This type of research is descriptive. The sample of the study was housewives with HIV AIDS at Reproductive Health Center in Merauke with 30 respondents with total sampling. The majority of respondents were married (63.3%), aged < 35 years (60.0%), highly educated (60.0%), receiving family support (90.0%) and complying with ARV (83.3%). Housewives with HIV AIDS at Merauke hospitals receive family support and are obedient to taking ARVs. Keywords: housewife, ARV, HIV / AIDS